Prototype of Blind Aid Tool With The Haar Like Feature - Ade Bastian; Dony Susandi; Usup Suparma (IJISTECH (International Journal of Information System and Technology), 2020)
Every human being is born perfectly but not all humans are born perfect, some of us are born have a deficiency in blindness. Blind people are someone whose vision is impaired from birth or because of an illness that causes their vision to be disrupted. Blind people need tools for their daily activities usually in carrying out blind activities using tools as a tool. Tools that are now widely circulating only as a detector can not yet identify objects, for that blind people neeed a tool that can identify the object. To make this happen, a prototype design research is done. Blind assitive devices use the haar like feature and extreme contour methods. Prototyping method is chosen so that users can play an active role during the process of designing, testing and implementing tolls. Contour is a curve or image that has similarities with objects or objects with functions using OpenCv. The conclusion of the detection results using the haar like feature method is the form of a string then processed using pygame so that the blind are able to know the object in fron of it.